The Wolves of Willoughby Chase - Aiken, Joan (Random House Children book, 1962)
History that never happened. Good King James III is on the throne and the country is ravaged by wolves which have migrated through the newly-opened Channel Tunnel. When Sylvia and Bonnie (both orphans) fall into the hands of evil Miss Slighcarp, they must use all their wits to escape unscathed - for the governess is more cruel and merciless than the wolves that surround the great house of Willoughby Chase.
Keywords: Juvenile literature-Fiction